The Association Between Macular Thickness and Peripapillary Retinal Nerve Fiber Layer Thickness in Chinese Children - Lee, Jacky W.Y. (Medicine (Baltimore), 2015)
To investigate the association between macular thickness and peripapillary retinal nerve fiber layer (RNFL) thickness in Chinese children. This cross-sectional study recruited consecutive cases of healthy pediatric subjects aged 4 to 18 from Caritas Medical Centre in Hong Kong Special Administrative Region, China, from 2013 to 2014. Subjects with only eye, ocular tumors, congenital glaucoma, congenital cataract, congenital nystagmus, microphthalmos, optic nerve or retinal disease, active ocular infections, corneal scars, and severe visual impairment of any cause were excluded. Peripapillary RNFL thickness and macular thickness at 1-mm-diameter fovea center (C1), 3-mm-diameter temporal quadrant (T3), and 3-mm- diameter nasal quadrant (N3) were measured with optical coherence tomography. Best-corrected visual acuity, axial length, and cycloplegic refraction were also recorded. Spearman correlation was used to analyze the association between T3, C1, and N3 with each of the following: average and quadrant RNFL thickness, axial length, and spherical equivalent. In 179 subjects, the mean age was 7.9 ± 3.6 years. There were 90 male and 89 female subjects, all of Chinese ethnicity. The mean spherical equivalent was −0.1 ± 3.1 D and mean axial length was 22.9 ± 1.4 mm. There were significant and positive correlations of the average (T3: r = 0.20, P = 0.04; N3: r = 0.2, P = 0.005), superior (T3: r = 0.20, P = 0.03; N3: r = 0.2, P = 0.03), and inferior (T3: r = 0.20, P = 0.02; N3: r = 0.2, P = 0.01) peripapillary RNFL thicknesses with the T3 and N3 macular thicknesses but not C1. The nasal peripapillary RNFL thickness was also positively correlated with T3 (r = 0.20, P = 0.01). There were no significant associations between the macular thickness (T3, C1, N3) with neither the spherical equivalent (P > 0.2) nor the axial length (P > 0.3). The macular thickness was positive correlated with the peripapillary RNFL thickness in a population of healthy Chinese children.